Nutrition and Metabolic Support Recommendations for the Bariatric Patient. (December 2014) - Isom, Kellene A.; Andromalos, Laura; Ariagno, Meghan; Hartman, Katy; Mogensen, Kris M.; Stephanides, Katrina; Shikora, Scott
Managing the metabolic needs of the patient with obesity is a challenge unto itself without the added demands of accounting for an altered gastrointestinal tract. Nevertheless, with about 200, 000 bariatric procedures being performed annually in the United States, clinicians must be prepared to manage the critically ill bariatric surgery patient. This article reviews the recent literature relating to nutrient needs and metabolic support for the bariatric patient. Bariatric patients are at risk for several micronutrient deficiencies, including vitamins D and B12, calcium, and iron; some bariatric procedures affect macronutrient needs as well. Literature on nutrition support guidelines for the bariatric population is limited. However, with an understanding of the anatomical and physiological effects of bariatric surgery, recent guidelines for critically ill patients with obesity can be applied to the bariatric surgery population. The unique needs of the bariatric population, such as susceptibility to micronutrient deficiencies and specialized access routes, must be considered to provide safe and efficacious nutrition support. Further research is necessary to develop specific nutrition support recommendations for the bariatric population.